Anlotinib for Patients With Metastatic Renal Cell Carcinoma Previously Treated With One Vascular Endothelial Growth Factor Receptor-Tyrosine Kinase Inhibitor: A Phase 2 Trial - Ma, Jianhui; Song, Yan; Shou, Jianzhong; Bai, Yuxian; Li, Hanzhong; Xie, Xiaodong; Luo, Hong; Ren, Xiubao; Liu, Jiyan; Ye, Dingwei; Bai, Xianzhong; Fu, Cheng; et al. (Frontiers in Oncology, 2020)
Introduction: Sequential therapy with vascular endothelial growth factor receptor-tyrosine kinase inhibitors (VEGFR-TKIs) is effective in some patients with metastatic renal cell carcinoma (mRCC) progressed from or were intolerant to a prior TKIs. Anlotinib is a multi-kinase inhibitor targeting VEGFR1/2/3, PDGFR and FGFR, which has demonstrated efficacy and safety in first-line treatment of mRCC. This study assessed the potential of anloitnib as second-line treatment for patients with mRCC after prior one VEGFR-TKI. Methods: This is a single-arm, open-label, phase 2 study. Patients progressed after or were intolerant to sorafenib or sunitinib were enrolled. Anlotinib was administrated orally 12 mg once daily for 14 days every three weeks. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS), objective response rate (ORR), safety and quality of life (QoL). Results: 43 patients were enrolled and 42 received anlotinib, of whom 32 progressed after and 10 were intolerant to sorafenib or sunitinib. Median PFS were 14.0 months (95% CI 8.3-20.3) and 8.5 months (95% CI 5.6-16.6) for overall population and patients progressed after a previous VEGFR-TKI respectively. Median OS was 21.4 months (95% CI 16.0-34.5), confirmed ORR and DCR were 16.7% and 83.3% in overall population. The most common adverse events included diarrhea (47.6%), hypertension (45.2%), hand and foot syndrome (42.9%) and fatigue (40.5%). Grade 3 hematological adverse events occurred in four cases, while no grade 4 adverse event was observed. Conclusions: Anlotinib showed promising efficacy as well as favorable safety as second-line treatment for patients with mRCC.